Legislation on Disability and Employment: To What Extent Are Employment Rights Guaranteed for Persons with Disabilities? - Mónica Pinilla-Roncancio (International Journal of Environmental Research and Public Health, 2022)
Although the Convention on the Rights of Persons with Disabilities guarantees the right to employment and most countries in Latin America have signed and ratified the Convention, a large proportion of the population with disabilities still does not participate in the labour market. (1) Objective: The objective of this research was to understand how legislation in seven Latin American countries (Bolivia, Costa Rica, Chile, Colombia, Ecuador, Mexico, and Peru) has defined and enabled the inclusion of people with disabilities in the labour market. (2) Methods: We conducted a thematic analysis of the content of 34 documents and generated two thematic networks that summarise the results of the thematic analysis and represent the general relationships between the categories of analysis in each country. Using this information, we analysed the differences between countries and the advance in their legislation to fulfil the recommendations made by the Convention. (3) Results: Although all countries have enacted legislation promoting the employment rights of persons with disabilities, six of the seven countries (except Chile) have applied a medical perspective to the definition of disability in their labour legislation, thus imposing a barrier to the labour-market inclusion of this population and perpetuating the association of disability with lack of capacity to work.